Hybrid SWARA-COPRAS method for risk assessment in deep foundation excavation project: an iranian case study - Valipour, Alireza; Yahaya, Nordin; Md Noor, Norhazilan; Antuchevičienė, Jurgita; Tamošaitienė, Jolanta (Journal of Civil Engineering and Management, 2017)
Existing risks in deep foundation excavation projects is a major issue in developing cities. With the rapid in-crease in the number of various deep foundation and excavation projects in big cities of Iran, many accidents related to deep excavation have been reported every year. These accidents affected delay and increased cost of project implemen-tation. Therefore identification and assessment of risks of these accidents is essential. The aim of the research was to develop a framework to overcome limitations of previous approaches to assess of risks in excavation projects. According to the complexity of a problem and the inherent uncertainty, the framework adopted SWARA (Step-wise Weight As-sessment Ratio Analysis) and COPRAS (COmplex PRoportional ASsessment) methods through introducing new criteria for risk assessment. Data was collected through interview, a literature review and a questionnaire survey distributed to excavation project experts. A case study of deep foundation excavation in Shiraz was presented. The results have shown that the risks involving construction safety, unfavourable geological conditions, shortage of managerial experience, in-complete emergency plan and subsidence of ground are the most significant risks excavation projects in Shiraz. The proposed framework and the obtained results can help stakeholders of excavation projects in developing countries better to manage project risks.